Odpowiedź :
a)
[tex](3x-y)^2-(3x-2y)(3x+2y)=9x^2-6xy+y^2-(9x^2-4y^2)=\\=9x^2-6xy+y^2-9x^2+4y^2=-6xy+5y^2[/tex]
b)
[tex](p-2q)^3+(p+2q)^3=p^3-6p^2q+12pq^2-8q^3+p^3+6p^2q+12pq^2+8q^3=\\=2p^3+24pq^2[/tex]
c)
[tex]b(3a-2b)2-(2b-a)^3=(3ab-2b^2)2-(8b^3-12ab^2+6a^2b-a^3)=\\=6ab-4b^2-8b^3+12ab^2-6a^2b+a^3[/tex]
Chyba, że w c) jest błąd i miał być pierwszy nawias do potęgi drugiej, wtedy:
[tex]b(3a-2b)^2-(2b-a)^3=b(9a^2-12ab+4b^2)-(8b^3-12ab^2+6a^2b-a^3)=\\=9a^2b-12ab^2+4b^3-8b^3+12ab^2-6a^2b+a^3=3a^2b-4b^3+a^3[/tex]